The Effect of moving Tongue and Lips on Certain Shariah Rulings - Bint Abdul Mohsen Ben Said, Sarah (الدراسات الإسلامية, 2020)
This research work relates to the differences between verbal reading and just thinking of or seeing a text and their implications with respect to validity or otherwise of certain rituals. In Islamic law just thinking of a text or seeing it without moving tongue or lips is not considered proper reading with respect to the non-disabled persons and does not fulfill the requirement where proper reading is required. Therefore, it is necessary to move the tongue and lips during the recitation of the Qur’an in the prayer, which is an obligatory part of the prayer. Speech-impaired persons and those who are unable to move their tongues are, however, exempted from this obligation. The objective of this research is to clarify the meaning of proper reading and differentiate it from just thinking of or seeing a text and its implications for certain Islamic obligation. The research methodology adopted in this research work is descriptive and analytical and entails of library research. Keyword Reading, Silence, Tongue, Validity, Islamic Law